Evaluation of Incurred Subject Period Re-analysis (ISPR) as a Tool to Distinguish Fraudulent Pharmacokinetic Profile Pairs from Non-fraudulent Pairs - Fuglsang, Anders; Dogra, Anshul; Sharma, Naveen (The AAPS journal, 2024)
Duplicate pharmacokinetic profiles in bioequivalence trials is an issue which has caused hundreds of retracted marketing authorizations. No formal test for profile duplication exists in spite of the existence of profile comparison algorithms, so defining a threshold that distinguishes a naturally occurring pair from a duplication remains difficult. An idea called ISPR (incurred subject period analysis) was aired in 2023 and is evaluated in this paper along with three new profile comparison methods. ISPR involves analysis of entire PK-profiles within a study. It is shown that when ISPR is combined with appropriate PK-profile comparison methods, the duplicate pairs display a lower score (better similarity) than pair that do not arise out of duplication. Therefore, ISPR may help establish a threshold that distinguishes fraudulent profile pairs from non-fraudulent profile pairs. ISPR therefore may be used as QA tool, serves as a method by which a CRO can -to some extent- show that their studies do not contain duplicates in the primary analysis, and thus also may be a means by which sponsor can argue that their studies are trustworthy, in case the suspicion about duplication arises. This paper does not introduce a formal test for this type of fraud; rather the authors see it as a first moderate step in that direction. Hopefully, if or when ISPR data is submitted to authorities as part of general dossier submission, data will accumulate to the extent that they may be able to develop models that allow formal testing for profile duplication.